Global Index of Vulnerability to Earthquake to the towns of Lorca and Totana, Spain - Sophie Mendizabal (PANGAEA, 2020)
This data proposes a Global Index of Vulnerability to Earthquake (GIVE) of educational institutions of the towns of Lorca and Totana located on the active Alhama de Murcia fault in the region of Murcia of the south-eastern Spain considering social and structural risk factors against seismic disaster. The results have been discretized into three classes: a low vulnerability and a high level of preparedness if 0 ≤ GIVE ≤ 1 ; a moderate vulnerability and a moderate level of preparedness if 1 < GIVE ≤ 2 ; a high vulnerability and a low level of preparedness if 2 < GIVE ≤ 3.